Management development: a new role in social change? - Clarke, Martin (Emerald, 1999)
Traditional approaches to organizational change are of little use in the bid for increased innovation as they reinforce top-down predictability. An alternative approach is through the creation of pockets of good practice which act as role models of change. These pockets need to be subversive of existing practices but simultaneously deliver organizational success criteria. The success of this approach is dependent upon managers developing a critical perspective about organizational control systems. Contrary to received wisdom the foundation for this critical perspective may be most usefully developed from the manager’s own cynical experience of organizational life. In building this critical perspective management development may begin to fulfil a wider educational role in society.
Keywords: Cynicism; Management development; Organizational change; Pockets of good practice; Subversion